Preference and consumption rate of the tropical abalone, Haliotis asinina, Linne, on selected macroalgae sp. - Uy, Christopher Sebastian Jaranilla
Limited stocks of harvestable seaweeds and the lower growth rates of other artificially cultured abalone species have stimulated research on suitable feed algae and the development of artificial diets. The aims of this investigation were (1) to determine which among the three macroalgal species, namely Gracilaria chilensis (Bird, McLachlan et Oliveira), Gracilariopsis heteroclada (Zhang et Xia), and Enteromorpha intestinalis (Linn.), is the most prefered by abalone Haliotis asinina Linn{82}; and (2) to determine how much of each of the three feed macroalgal species is actually consumed by the abalone., The abalone were housed in pail cages submerged in raceways with flow-through aerated seawater. Feeding (about 50 body weight of the abalone) was done every day for seven days. This study showed the order of preference to be: the green alga E. intestinalis, followed by the red algae G. heteroclada, and G. chilensis. Consumption rates (in body weight per day) were significantly different (P<0.05) for all three species of macroalgae, with values of 19.8 {ogon} 0.8 {ogon} 0.2, and 5.6 {ogon} 0.4 for E. intestinales, G. heteroclada, and G. chilensis, respectively. Feed consumption reached up to 35.0 {ogon} 1.2 on a mixed diet composed of the three macroalgal species. Proximate analyses showed that G. chilensis had both the highest protein, fat and carbohydrate content. The most preferred was E. intestinales, which had the lowest protein, fat, and carbohydrate, but the highest ash and moisture content.